Anterior cervical discectomy and fusion, open-door laminoplasty, or laminectomy with fusion: Which is the better treatment for four-level cervical spondylotic myelopathy? - Zhong, Huajian; Xu, Chen; Wang, Ruizhe; Wu, Xiaodong; Wu, Huiqiao; Sun, Baifeng; Wang, Xinwei; Chen, Huajiang; Shen, Xiaolong; Yuan, Wen (Frontiers in Surgery, 2023)
Four-level cervical spondylotic myelopathy (CSM) is a common disease affecting a large number of people, with the optimal surgical strategy remaining controversial. This study compared the clinical outcomes, radiological parameters, and postoperative complications of primarily performed surgical procedures such as anterior cervical discectomy and fusion (ACDF), open-door laminoplasty (LAMP), and laminectomy with fusion (LF) in treating four-level CSM. A total of 116 patients who received ACDF (38 cases), LAMP (45 cases), and LF (33 cases) were followed up for a minimum of 24 months were enrolled in this study and retrospectively analyzed. Clinical outcomes were evaluated using the Japanese Orthopedic Association (JOA) scoring system, the Neck Disability Index (NDI), and the Visual Analogue Scale (VAS). Changes in the curvature of the cervical spine were determined using the cervical curvature index (CCI) and the C2–C7 Cobb angle. Cervical mobility was evaluated using the C2–C7 range of motion (ROM) and active cervical ROM (aROM). Complications were recorded and compared among the three groups. All patients achieved significant improvement in JOA, NDI, and VAS scores at the final follow-up (P < 0.05), whereas no remarkable difference was found among the groups (P > 0.05). In addition, both C2–7 ROM and aROM were significantly reduced in the three groups and LAMP showed the least reduction relatively. As for complications, LAMP showed the lowest overall incidence of postoperative complications, and patients in the ACDF group were more susceptible to dysphagia, pseudoarthrosis than LAMP and LF. Considering improvements in clinical symptoms and neurological function, no remarkable difference was found among the groups. Nevertheless, LAMP had advantages over the other two surgical procedures in terms of preserving cervical mobility and reducing postoperative complications.